Effects of melt cooling rate on the microstructure and mechanical properties of Al-Cu alloy. (25th September 2019) - Wang, Lin; Sun, Yu; Bo, Lin; Zuo, Min; Zhao, Degang
Abstract: In this study, effects of cooling rate on the solidification microstructure and mechanical properties of Al-Cu alloys were investigated by casting in different molds (sand/steel/copper molds). The phase composition, thermodynamic phase transition process and mechanical properties of Al-Cu alloys were studied. The cooling rate has a significant effect on the morphology of primary α -Al phase and θ -Al2 Cu phase. When the cooling rate increases, the microstructure is significantly refined and the mechanical properties of Al-Cu alloys are improved. As the Cu content increases before the eutectic point, the content of primary α -Al phase in the alloy decreases to a small amount, and the hardness increases correspondingly as the ratio of intermetallic θ -Al2 Cu phase increases in the whole solidified microstructure. In addition, the thermal reaction of Al-Cu alloys was determined according to the peak temperature in the DSC curves, and the results were consistent with the solidification morphology. When the cooling rate is faster, the peak area of DSC curve of Al-Cu alloys is smaller than that of the corresponding sand-cooled sample. It is expected to provide a beneficial guidance for the preparation and application of heat-resistant Al-Cu alloy in the field of foundry alloys.